Agriculture for nutrition: Direct and indirect effects - Headey, Derek D.; Masters, William A. (International Food Policy Research Institute, 2019)
This chapter describes three main channels through which changing agriculture can affect nutrition: • the level and stability of real income and purchasing power among poor people; • the relative cost and difficulty of acquiring more nutritious foods relative to other things; and • exposure to health hazards associated with agricultural production, including various pathogens but also other harmful agricultural practices.